2020
DOI: 10.18844/cjes.v15i3.4906
|View full text |Cite
|
Sign up to set email alerts
|

Effects of piano accompaniment on instrument training habits and performance self-efficacy belief in flute education

Abstract: Education methods to be used in the emotional, mental and psychological development of instrument education are of great importance in terms of education process. In this context, the training habits and self-efficacy developments of the students with their instruments can be supported by the accompaniment education process, thus increasing the performance of the instruments. In this context, an experimental method was used in the research by using piano accompaniment training practice, individual instrument t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…is teaching method fully respects students' individuality, mobilizes students' initiative and innovation, and encourages students to use various learning tools, think independently, draw inferences from one case, and reasonably construct their own knowledge system and performance style. e traditional teaching method of the accompaniment art small class often omits the partner, and the teacher and the students only teach the accompaniment part, ignoring the internal and external connection between the singing (the sound of the piano) and the piano accompaniment, and cannot form a tacit cooperation and joint research on the works [3].…”
Section: Teaching Methods Design Of Practical Classmentioning
confidence: 99%
See 2 more Smart Citations
“…is teaching method fully respects students' individuality, mobilizes students' initiative and innovation, and encourages students to use various learning tools, think independently, draw inferences from one case, and reasonably construct their own knowledge system and performance style. e traditional teaching method of the accompaniment art small class often omits the partner, and the teacher and the students only teach the accompaniment part, ignoring the internal and external connection between the singing (the sound of the piano) and the piano accompaniment, and cannot form a tacit cooperation and joint research on the works [3].…”
Section: Teaching Methods Design Of Practical Classmentioning
confidence: 99%
“…e piano accompaniment can also be used in the ensemble of ethnic musical instruments, fully integrating a Western imported product such as the piano into the ethnic music culture and using the 88 black and white keys of the piano to authentically play the charm of ethnic music, which makes this music. e charm of a variety of folk music sprinkles between each note [3].…”
Section: Clarify the Professional Functions Of Piano Accompaniment An...mentioning
confidence: 99%
See 1 more Smart Citation
“…After the course of the experiment, he used a t-test to get the scores for each group. e results showed that the application of piano accompaniment in flute education had a positive effect on all subdimensions of both questionnaires [4]. Lee et al proposed an automatic melody extraction algorithm using deep learning.…”
Section: Related Workmentioning
confidence: 98%